Recent Advances on the Posttranslational Modifications of EXTs and Their Roles in Plant Cell Walls - Velasquez, Silvia M.; Salgado Salter, Juan; Petersen, Bent Larsen; Estevez, Jose M. (Frontiers in Plant Science, 2012)
The genetic set up and the enzymes that define the O-glycosylation sites and transfer the activated sugars to the cell wall protein backbone have remained unknown for a long time. We are now beginning to see the emerging components of the molecular machinery that assembles these complex O-glycoproteins on the plant cell wall. Genes conferring the posttranslational modifications, i.e. proline hydroxylation and subsequent O-glycosylation, of the plant cell wall protein extensin subgroup have being recently identified. In this review we summarize the enzymes that define the O-glycosylation sites on the O-glycoproteins, i.e. the prolyl 4–hydroxylases (P4Hs), the glycosyltransferases that transfer arabinose units (named arabinosyltransferases, AraTs) and the one responsible for the transfer of a single galactose (galactosyltransferase, GalT) on the protein extensin backbones, and finally the EXT peroxidase-mediated crosslinking at the cell wall. We discuss the effect of posttranslational modification on the structure and function of extensins in the plant cell walls.